SENYAWA KUERSETIN SEBAGAI AGEN ANTIKANKER KOLOREKTAL SECARA IN SILICO - P. V. P. Putri; N. M. P. Susanti; N. P. L. Laksmiani (Jurnal Kimia (Journal of Chemistry), 2019)
Colorectal cancer is a third rank malignant cancer in Indonesia, generally caused by the diet of the Indonesian people who have change with the consumption of food with high fat and low in fiber, also due to the production of carcinogenic substances from the breakdown of fat. In the condition of colorectal cancer there is overexpression of COX-2 and inhibition of Caspase-3 which causes the increase of cancer cells survival and causes inhibition of apoptosis mechanism. Quercetin is one of flavonoid which known have activity as an antitumor and tested in vitro can induce apoptosis on WiDr colorectal cancer cells . The purpose of this study was to determine the affinity and mechanism of quercetin compounds on COX-2 and Caspase-3 target proteins as colorectal anticancer by in silico with molecular docking. The study was conducted exploratively with the stages of preparing a database of 3D quercetin structures, as well as COX-2 and Caspase-3 proteins, optimization of 3D quercetin structure, protein preparation, molecular docking method validation, and quercetin docking on these proteins. Docking results were assessed from the binding energy and hydrogen bonds that formed between quercetin with proteins. The smaller binding energy value, the stronger the bond between quercetin and proteins is. The results showed that quercetin had an activity as a colorectal anticancer because it was able to inhibit COX-2 and induce Caspase-3 with binding energy values of -9.54 and -4.59. These results showed that quercetin has the potential to induce apoptosis in colorectal cancer. Keywords: colorectal cancer, quercetin, caspase-3, in silico